2006
DOI: 10.1182/asheducation-2006.1.133
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Adult Acute Lymphoblastic Leukemia

Abstract: In the early 1980s, adult acute lymphoblastic leukemia (ALL) was a rarely curable disease with overall survival < 10%. After adapting combinations employed by pediatric groups, the outcome improved to 30-40%. A period of stagnation followed with improvement only in distinct subgroups. In the past 5 years, however, striking new developments have been noticeable. Progress has been made in molecular diagnostics of ALL. Improvements to standard therapy including stem cell transplantation (SCT) have occurred and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
82
1
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(89 citation statements)
references
References 34 publications
1
82
1
5
Order By: Relevance
“…However, the overall survival rate is only 27-48% because of the high rate of relapse. 1 Therefore, the establishment of optimal postremission therapy is important. The efficacy of allogeneic hematopoietic stem cell transplantation (HSCT) for adult patients with ALL in first remission has been demonstrated through clinical studies using genetic randomization, in which patients with a human leukocyte antigen (HLA)-matched sibling donor were allocated to the allogeneic HSCT arm, and those without a donor were placed in the chemotherapy or autologous transplantation arm.…”
Section: Introductionmentioning
confidence: 99%
“…However, the overall survival rate is only 27-48% because of the high rate of relapse. 1 Therefore, the establishment of optimal postremission therapy is important. The efficacy of allogeneic hematopoietic stem cell transplantation (HSCT) for adult patients with ALL in first remission has been demonstrated through clinical studies using genetic randomization, in which patients with a human leukocyte antigen (HLA)-matched sibling donor were allocated to the allogeneic HSCT arm, and those without a donor were placed in the chemotherapy or autologous transplantation arm.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In addition, great progress has been made in understanding the biology of ALL: recently, genome-wide analyses of ALL patients showed deletions and mutations of genes associated with lymphoid development, such as LEF1, TCF, PAX5, IKAROS and NOTCH1. [3][4][5] However, for the majority of ALL cases the molecular mechanisms driving the malignant transformation are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…49 Anti-CD20 antibodies are not effective in treating such patients, whereas anti-CD19 MAbs might be. In our study, we demonstrated that in vitro the cHD37 MAbs mediated apoptosis, ADCC and ADCP against human pre-B ALL NALM-6 and KOPN-8 cells, and in vivo, extended the MPT of SCID mice xenografted with NALM-6 cells, indicating that these MAbs should have the potential of treating humans with pre-B ALLs.…”
Section: Discussionmentioning
confidence: 99%